SYSTEMATIC LITERATURE REVIEW: PENGARUH TERAPI GARLIC (ALLIUM SATIVUM L) TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI - Lilis Upate; Nur Baharia Marasabessy (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2023)
Background: Hypertension is a manifestation of hemodynamic balance disorders. Hypertension cannot be cured but can be controlled, one method of controlling hypertension is non-pharmacological therapy using garlic (Allium sativum L). Garlic is a kitchen spice that is always present in the family and is easy to implement for family members who suffer from hypertension because of the ability of garlic to significantly reduce the risk of hypertension. Objective: This study aims to determine the effect of garlic (Allium sativum L) therapy on reducing blood pressure in patients with hypertension through library research. Method: Narrative review. Literature search using certain keywords in two databases, namely google schoolar and pubmed, with inclusion criteria: full text articles, in Indonesian or English from 2018-2022, subjects were people with hypertension, research types are Quasy Experiments and RCTs. Results: a study of 8 articles showed that therapy using garlic (Allium sativum L) in the form of extracts, infusions or capsules was able to reduce blood pressure in patients with hypertension. Conclusion: there is an effect of garlic (Allium sativum L.) therapy on reducing blood pressure in patients with hypertension.